2012
DOI: 10.1007/s00277-012-1429-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase II prospective study of treosulfan-based reduced-intensity conditioning in allogeneic HSCT for hematological malignancies from 10/10 HLA-identical unrelated donor

Abstract: Different RIC regimens were evaluated prior to allo-HSCT in different hematological malignancies. We conducted this prospective study in adult patients with various hematological malignancies in order to evaluate the toxicity and efficacy of treosulfan-based conditioning, followed by allo-HSCT from 10/10 HLA-identical unrelated donors. Conditioning included treosulfan 12 g/m(2)/day i.v. (day -6 to day -4), fludarabine 30 mg/m(2)/day i.v. (day -6 to day -2), and ATG 2.5 mg/kg/day (day -2 to day -1). PBSC were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
3
9
0
Order By: Relevance
“…However, it should be noted that 1 heavily pretreated patient with AML/MDS in the FluTreoATG group presented post-transplantation lymphoproliferative disorder. Similar cases have been previously reported after treosulfan conditioning in unrelated transplantations [27,28]. Therefore, cautious management of EBV reactivation in patients receiving ATG is advisable.…”
Section: Discussionsupporting
confidence: 81%
“…However, it should be noted that 1 heavily pretreated patient with AML/MDS in the FluTreoATG group presented post-transplantation lymphoproliferative disorder. Similar cases have been previously reported after treosulfan conditioning in unrelated transplantations [27,28]. Therefore, cautious management of EBV reactivation in patients receiving ATG is advisable.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, while improvements in supportive care over the years may contribute to favorable outcome, several studies found improved OS with treosulfan-based conditioning in comparison to historical data 24,4244 . Ruutu et al and Casper et al showed 2-year NRM of 17% and 11%, and OS of 71% and 61%, respectively, in patients with MDS or AML conditioned with treosulfan/fludarabine and transplanted from HLA-matched related or unrelated donors 24,38 .…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative incidence of relapse was 25% at 3 years and the NRM at 12 and 24 months was 20% and 23%, respectively. 30 The studies from groups in Germany and Israel has shown promising efficacy with TREO-based regimens. 31,32 Kroger et al 31 investigated a dose-reduced conditioning regimen consisting of TREO and FLU followed by allo-HSCT in 26 patients with secondary AML or MDS.…”
Section: Busulfan Cyclophosphamide (Bu-cy) Vs Cyclophosphamide Tbi mentioning
confidence: 99%